Legal Role By the National Land Agency of Labuhanbatu District in the Settlement Land Disputes in Regency Area Labuhan Batu - Dhiky Bryan Harpinansah; Bernat Panjaitan; Nimrot Siahaan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to know as well as analyze about Role Law of the District National Land Agency Labuhanbatu in finish dispute land in the district area Labuhanbatu.Besides That know as well as analyze about obstacles that occur in settlement dispute land that occurs in the working area of the Regency National Land Agency Labuhanbatu. This Research including type study juridical empirical, or called with study field that is study provision applicable law as well as what happened in fact in society. Results of the discussion is role the law of the Regency National Land Agency Labuhanbatu in finish dispute land in the district area Labuhanbatu can taken with two method ie non litigation and litigation. Furthermore, the obstacles that occur in settlement dispute land that occurs in the working area of the Regency National Land Agency Labuhanbatu as following: exists party that doesn't have faith No well, low level participation party dispute in finish dispute land, Lack Source Power Human, No exists strict sanctions from the BPN if happen one intention disputing parties.